Survival of Escherichia Coli O157:H7 and Salmonella Enterica Serovar Typhimurium in Manure and Manure-Amended Soil under Tropical Climatic Conditions in Sub-Saharan Africa - Ongeng, D.; Muyanja, C.; Geeraerd, A.H.; Springael, D.; Ryckeboer, J. (Journal of applied microbiology, 2011)
To establish the fate of Escherichia coli O157:H7 and Salmonella Typhimurium in manure and manure-amended agricultural soils under tropical conditions in Sub-Saharan Africa. Survival of nonvirulent E. coli O157:H7 and Salm. Typhimurium at 4 and 7 log CFU g−1 in manure and manure-amended soil maintained at ≥80% r.h. or exposed to exclusive field or screen house conditions was determined in the Central Agro-Ecological Zone of Uganda. Maintaining the matrices at high moisture level promoted the persistence of high-density inocula and enhanced the decline of low-density inocula in the screen house, but moisture condition did not affect survival in the field. The large majority of the survival kinetics displayed complex patterns corresponding to the Double Weibull model. The two enteric bacteria survived longer in manure-amended soil than in manure. The 7 log CFU g−1E. coli O157:H7 and Salm. Typhimurium survived for 49–84 and 63–98 days, while at 4 log CFU g−1, persistence was 21–28 and 35–42 days, respectively. Under tropical conditions, E. coli O157:H7 and Salm. Typhimurium persisted for 4 and 6 weeks at low inoculum density and for 12 and 14 weeks at high inoculum density, respectively.
Keywords: E. coli O157:H7, manure, manure-amended soil, Salmonella Typhimurium, survival, tropics